Pengaruh Pembelajaran Dalam Jaringan (Daring) Terhadap Motivasi Belajar Mahasiswa Kelas A Program Studi Pendidikan Agama Islam Sekolah Tinggi Agama Islam (STAI) Salahuddin Pasuruan Di Era Pandemi Covid-19 - Mukaromah, Ning (Academia Publication, 2021)
The purpose of this research is to determine whether online learning had a significant effect on learning motivation of class A students of the Islamic Education program in the Covid-19 pandemic era. This research uses a quantitative approach. The sample of this research are 54 Students in class A Islamic Education Program STAI Salahuddin Pasuruan. The data collection technique uses a questionnaire which is distributed by researchers by google form. The testing technique uses simple linear regression analysis. The results showed that there was a significant influence between online learning (X) on learning motivation (Y), because the value of t count> from the t table with a significant level of 5%, namely 6,057> 1,671. The contribution of online learning to the learning motivation of class A students of the Islamic Education Program of STAI Salahuddin was 41.4% and the remaining 58.6 was influenced by other factors not examined in this study.